DENTAL IMPLANTATION: ADVANTAGES, DISADVANTAGES, AND COMPLICATIONS - Abduraxmonova, Shohista (O‘RTA OSIYODA IJTIMOIY VA GUMANITAR TADQIQOTLAR, 2025)
This article examines the main aspects of dental implantation, including its advantages, disadvantages, and possible complications. Dental implants have become one of the most effective and long-lasting methods of restoring lost teeth in modern dentistry. The article analyzes the structure of implants, materials used, and the stages of the implantation procedure. The functional and aesthetic benefits of implants compared to traditional prosthetics are highlighted. In addition, potential risk factors, postoperative complications, and preventive measures to ensure successful osseointegration are discussed. Special attention is given to innovations in implant design, biocompatible materials, and digital technologies that increase treatment precision and success rates.